REVIEW : KARAKTERISTIK FISIK DAN DAYA IRITASI MINYAK ATSIRI BUNGA CENGKEH (Syzygium aromaticum) DALAM BEBERAPA TIPE BASIS SEBAGAI ANTI-INFLAMASI - Amraini Amelia; Nining Sugihartini; Hari Susanti (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
ABSTRACT This review aims to determine the types of bases that can be used every day, which are effective and efficient as anti-inflammatory drugs. The research method used was to review the development of clove essential oil formulations that have been carried out using various concentrations of various types of bases including M / A type cream, A / M type cream, water soluble base, lotion, emulgel, hydrocarbons, hydrogels and absorbents. The recommended formulation is type M / A cream with a concentration of 5% clove flower essential oil. The types of bases studied were M / A cream, type A / M cream, water soluble base, lotion, emulgel, hydrocarbons, hydrogels and absorption properties which had good physical properties and did not irritate the skin of the test animals. This review refers to several national and international journals released in the last ten years, from 2010 to 2020.